Export Spillovers of FDI on China's Domestic Firms. Issue 5 (22nd October 2013) - Chen, Chunlai; Sheng, Yu; Findlay, Christopher
Abstract: This paper examines the horizontal and vertical export spillovers of foreign direct investment (FDI) on China's manufacturing domestic firms by using firm‐level census data over the period of 2000–03. Based on a Heckman two‐step procedure combining first differencing and instrumental variable regression techniques, it is found that FDI has had a positive impact on the export value of domestic firms mainly through backward technology spillovers and a positive impact on the export‐to‐sales ratio of domestic firms through horizontal export‐related information spillovers. After decomposing FDI by different market orientation and domestic firms by different ownership, the paper finds that the positive impact on domestic firms' export values is mainly from the nonexporting and the exporting foreign‐invested enterprises while the positive impact on domestic firms' export‐to‐sales ratios is mainly from the high‐exporting foreign‐invested enterprises. Both types of export spillovers are mainly diffused to domestic non‐state‐owned enterprises.